Whole-genome resequencing of Dorper and Hu sheep to reveal selection signatures associated with important traits - Lv, Xiaoyang; Chen, Weihao; Wang, Shanhe; Cao, Xiukai; Yuan, Zehu; Getachew, Tesfaye; Mwacharo, Joram; Haile, Aynalem; Sun, Wei (Taylor and Francis Group, 2023)
Dorper and Hu sheep exhibit different characteristics in terms of reproduction, growth, and meat quality. Comparison of the genomes of two breeds help to reveal important genomic information. In this study, whole genome resequencing of 30 individuals (Dorper, DB and Hu sheep, HY) identified 15,108,125 single nucleotide polymorphisms (SNPs). Population differentiation (Fst) and cross population extended haplotype homozygosity (XP-EHH) were performed for selective signal analysis. In total, 106 and 515 overlapped genes were present in both the Fst results and XP-EHH results in HY vs DB and in DB vs HY, respectively. In HY vs DB, 106 genes were enriched in 12 GO terms and 83 KEGG pathways, such as ATP binding (GO:0005524) and PI3K-Akt signaling pathway (oas04151). In DB vs HY, 515 genes were enriched in 109 GO terms and 215 KEGG pathways, such as skeletal muscle cell differentiation (GO:0035914) and MAPK signaling pathway (oas04010). According to the annotation results, we identified a series of candidate genes associated with reproduction (UNC5C, BMPR1B, and GLIS1), meat quality (MECOM, MEF2C, and MYF6), and immunity (GMDS, GALK1, and ITGB4). Our investigation has uncovered genomic information for important traits in sheep and provided a basis for subsequent studies of related traits.